A view from the bridge - Adler, Luther, 1903-1984; Evans, Charles; Miller, Arthur, 1915-2005 (1960)
National Theatre, Louis A. Lotito, managing director, I.L. Kamens & Paul Stoudt present the Luther Adler production, Luther Adler in Arthur Miller's "A View From the Bridge," with Alan Mixon, Kathleen Widdoes, Louis Zorich, Paul Haney, Pearl Pearson, Carmen Costi, Tom Leith, Len Birman, staged by Mr. Adler, setting & lighting by Charles Evans.